Sintesis dan Karakterisasi Hidrogel Limbah Onggok dan Polyvinyl Alcohol (PVA) mengandung Ekstrak Lada sebagai Pemballut Luka Antibakteri - Rokar, Risna Kirana; Puspita, Indah; Indriawati, Anisa (Jurusan Fisika, Universitas Bangka Belitung, 2025)
Wound healing is a complex biological process in which wound dressings play a vital role in providing protection and supporting tissue regeneration. In this study, cassava dregs waste was utilized as a base material for the development of hydrogel wound dressings. The hydrogel was incorporated with black pepper (Piper nigrum) extract to enhance its antibacterial properties. Sample preparation consisted of several stages, including cassava dregs processing, hydrogel synthesis, and extraction of black pepper using the maceration method. The hydrogel was characterized in terms of swelling capacity, gel fraction, swelling kinetics, antibacterial activity against Staphylococcus aureus, functional group identification using Fourier Transform Infrared (FTIR) spectroscopy, and morphological analysis. The results demonstrated that the incorporation of black pepper extract significantly affected the swelling behavior of the hydrogel, with swelling capacities ranging from 263.76% to 387.87%. The hydrogel exhibited a high gel fraction of 86.13% and favorable swelling kinetics with a kinetic constant of 0.5443. Variations in black pepper extract volume were evaluated, including 0 ml (control), 20 ml, 40 ml, and 60 ml. These findings indicate that cassava dregs–based hydrogels enriched with black pepper extract have promising potential as antibacterial wound dressing materials.